Central and Eastern European Literary Theory and the West - Michał Mrugalski; Schamma Schahadat; Irina Wutsdorff (De Gruyter, 2022)
Literary theory flourished in Central and Eastern Europe throughout the twentieth century, but its relation to Western literary scholarship is complex. This book sheds light on the entangled histories of exchange and influence both within the region known as Central and Eastern Europe, and between the region and the West. The exchange of ideas between scholars in the East and West was facilitated by both personal and institutional relations, both official and informal encounters. For the longest time, however, intellectual exchange was thwarted by political tensions that led to large parts of Central and Eastern Europe being isolated from the West. A few literary theories nevertheless made it into Western scholarly discourses via exiled scholars. Some of these scholars, such as Mikhail Bakhtin, become widely known in the West and their thought was transposed onto new, Western cultural contexts; others, such as Ol'ga Freidenberg, were barely noticed outside of Russian and Poland. This volume draws attention to the schools, circles, and concepts that shaped the development of theory in Central and Eastern Europe as well as the histoire croisée – the history of translations, transformations, and migrations – that conditioned its relationship with the West.